PILOT PLANT FOR PRODUCTION OF FISH ENSILAGE AND THE ECONOMICS Of PRODUCTION - CHAKRABORTY, P K; JAMES, M ARUL (Fishery Technology, 2017)
This communication describes the design aspect andfunctions of individual pieces of equipment of a pilot plantfor the production of fish ensilage based on lactic acidfermentation process. Details about the equipment, processflow sheet and equipment layout of the pilot plant have beengiven. An attempt has been made to prepare an estimate ofthe cost of production of liquid ensilage and solid feed mix.